INTEGRATION APPROACH AS A MEANS OF IMPROVING THE QUALITY OF PROFESSIONAL TRAINING OF THE FUTURE TEACHER - MUSICIAN - Багрій, Т.Є. (SWorldJournal, 2022)
The abstracts cover the implementation of an integrative approach in the educational process. The model of professional training of the future teacher-musician is considered.